Effect of Chemical Fertilizer and Humic Acid on the Growth and Development of Paulownia tomentosa Seedlings. - Nigar Abdulrahman Sabir; Sherzad Omar Hamad (Zanco Journal of Pure and Applied Sciences, 2022)
Silvicultural treatments were applied in forest nursery to produce high quality and quantity seedlings. Fertilizer application is one of the most important treatments that were used to improve seedling morphological and physiological traits. The study investigated the influence of NPK fertilizer levels viz. 0, 0.5, 1, and 1.5 g pot-1, Humic acid levels viz. 0, 5, 10 and 15 g pot-1 and their interactions on growth and physiological properties of Paulownia tomentosa. Morphological growth parameters (the increment in the stem height, stem diameter and leaf number) and physiological parameters (leaf area, chlorophyll content and protein percent, and N, P, K content) were measured. The results indicate that the highest values of stem height and stem diameter increment were (52.70 cm and 10.69mm) at (1.5g) of NPK fertilizers. The maximum values of both traits were (51.40 cm and 10.33mm) recorded at (15g) of Humic acid. The highest mean value of nitrogen (2.90 and 2.53 %) reported from application of (1.5 g NPK and15g Humic acid), respectively. Among physiological parameters chlorophyll content recorded the highest value which were (56.97 and 56.04) at (1.5g NPK and 10g Humic acid,) respectively. From interaction between (1g NPK x 15g Humic acid) recorded the highest value of potassium which was (3.74%). The results will help will improve nursery practices to produce healthy and a high quality of P. tomentosa seedlings to meet the plantation programs.